2003
DOI: 10.1023/a:1025564930088
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previous studies in our laboratories have demonstrated that niacin-bound chromium (NBC), Maitake mushroom and (-)-hydroxycitric acid (HCA-SX) can ameliorate hypertension, dyslipidemias and diabetes mellitus, and therefore may be useful in weight management. In the present study, we used aged, diabetic Zucker fatty rats (ZFR) (70-75 weeks) in order to determine whether NBC, fraction SX of Maitake mushroom (MSX) and 60% (-)-hydroxycitric acid (HCA-SX) from Garcinia cambogia, alone or in combination, can affect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Accordingly, this makes the maitake mushroom and its commercial extracts excellent candidates to produce a long, healthful life span 42.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this makes the maitake mushroom and its commercial extracts excellent candidates to produce a long, healthful life span 42.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneously hypertensive rats (SHR) were obtained from Taconic Farms, Germantown, NY. SHR were chosen, because they develop various manifestations of the metabolic syndrome while consuming diets heavily laden with sucrose [16]. Two separate studies were performed.…”
Section: Protocolmentioning
confidence: 99%
“…Laboratory and clinical studies indicate that certain forms of trivalent chromium have the capability to: (a) increase fat loss while preserving muscle [9,10]; (b) overcome insulin resistance and ameliorate diabetes [5,8]; (c) suppress free radical formation [11]; (d) lower total cholesterol and low-density lipoprotein (LDL) [12]; (e) decrease systolic blood pressure (SBP) [11,13]; (f) influence fluid and electrolyte balance [13]; (g) alter catecholamine metabolism [14] and (h) influence nitric oxide (NO) functions [15]. Finally, a recent report also suggests that trivalent chromium may increase useful lifespan, at least in rodents [16].…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of Asia, Japan, China, and Mexico, mushrooms are believed to have curative attributes () . Studies have demonstrated that the consumption of mushrooms or consumption of isolated bioactive constituents contained in mushrooms may promote health by improving immunity ( , ), lowering blood cholesterol and lipids ( ), reducing blood pressure ( ), attenuating blood glucose ( ), acting as a chemoprotectant ( 2 , 21 − 23 ), and having antibiotic activity () . It is important to note that many of these effects are dependent on the isolation of bioactive compounds, processing, and fruit maturity at time of harvest ( , ).…”
Section: Introductionmentioning
confidence: 99%